ANALISIS DAMPAK GAME ONLINE TERHADAP PRESTASI BELAJAR PESERTA DIDIK ( STUDI KASUS DI SDN PENGARADAN 03 KECAMATAN TANJUNG KABUPATEN BREBES ) - Nurhijah Nurhijah; Didik Tri Setiyoko; H. Agus Purnomo (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
This research was conducted at the SDN Pengaradan 03 Kecamatan Tanjung, Kabupaten Brebes. The purpose of this study is 1) To determine the learning achievement of students. 2) To determine the factors that influence student learning achievement. 3) To find out efforts to minimize online game play on learning achievement. This study uses a qualitative approach, while the data collection uses the interview method, observation method and documentation method. The results of this study are 1) Learning achievement in Pengaradan 03 Kecamatan Tanjung, Kabupaten Brebes elementary school is quite good, where the velue is taken based on the attitude of the students themselves, daily by the teacher, mid – semester exam score and end of semester scores ehere the score is used as reference in knowing achievement learn students. 2) Factors that affect student learning achievement come from the family environment. Where family is the main and most important factor in shaping the character of students and a supportive social environment will affect the growth and development of students well by directing positive things that will affect the achievement og learning achievement in school. 3) Efforts that must be made in minimizing online game play are to to provide direction and understanding of the impact that is caused in online games that are done excessively, making the game on of the alternative rewards for student who get good ahievements so that they can motivate students to keep learning.